Reviewing the Role of Artificial Intelligence in Cancer - Patil, Shankargouda; Moafa, Ibtisam Hussain; Mosa Alfaifi, Mona; Abdu, Abrar Mohammed; Jafer, Mohammed Abdurabu; Raju K, Lizbeth; Raj, A. Thirumal; Sait, Sadiq M. (Asian Pacific Journal of Cancer Biology, 2020)
Among the modern-day advancements in technology, artificial intelligence (AI) and machine learning have shown to possess a large number of applications in various fields including medicine. In the current era, cancer is one of the most common non-communicable diseases attributing to a large number of global deaths. Attempts to increase the mortality and morbidity of cancer has been ongoing research. The integration of Artificial intelligence into cancer research is being actively carried out and has provided very promising results. Major factors that play a vital role in improving cancer prognosis including early detection and accurate diagnosis employing various imaging and molecular techniques. The use of artificial intelligence as a tool in these areas has shown its potential to detect and diagnose with increased precision, which is just one of the many applications of AI in cancer research. The present review aims as delving into literature and enlisting the applications of artificial intelligence in various commonly occurring cancers.